2010
DOI: 10.1007/s12272-010-0708-1
|View full text |Cite
|
Sign up to set email alerts
|

Transdermal therapeutic system of isradipine: Effect of hydrophilic and hydrophobic matrix on In Vitro and Ex vivo characteristics

Abstract: Isradipine (ISDP) is an effective calcium channel blocker used in the treatment of hypertension. It undergoes extensive first pass metabolism and bioavailability through the oral route is only about 15 to 24%. Hence we attempted to develop a matrix type controlled transdermal drug delivery system for ISDP. Formulations A1, A2, A3 were composed of Eudragit RL100 and hydroxypropyl methyl cellulose (HPMC) in 1:3, 1:1, 3:1 ratios; A4, A5, A6 were composed of Eudragit RS100 and HPMC in 1:3, 1:1, 3:1 ratios. All six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…The film thickness appeared to decrease with decreasing ratio of the Methocel ® E15:Eudragit ® polymer in the formulations. These results are in agreement with those reported previously (31,32). The results of the flatness study showed that the formulation films had a negligible change in the length along the longitudinally cut edges, indicating a near 100% flatness.…”
Section: Physicochemical Properties Of the Filmssupporting
confidence: 93%
See 1 more Smart Citation
“…The film thickness appeared to decrease with decreasing ratio of the Methocel ® E15:Eudragit ® polymer in the formulations. These results are in agreement with those reported previously (31,32). The results of the flatness study showed that the formulation films had a negligible change in the length along the longitudinally cut edges, indicating a near 100% flatness.…”
Section: Physicochemical Properties Of the Filmssupporting
confidence: 93%
“…The moisture content and the moisture uptake values of the prepared films were found to be dependent on the incorporated hydrophilic polymer ratio. An increase in the moisture content and moisture uptake by polymeric films as a function of increasing levels of hydrophilic polymers has been reported earlier (18,31,32,39). A small amount of moisture in the films is thought to be essential to maintain the stability and integrity of the films and to prevent excessive drying (resulting in brittleness and cracking) of the films (18,39).…”
Section: Discussionmentioning
confidence: 78%
“…Different plasticizers such as glycerol, DBT and PG were incorporated at 20% w/w of polymer dry weight. Calculated amount of DTH was mixed with homogenous polymer solution and poured into a petri dish containing mercury [12,13]. A funnel was placed over the petri dish in inverted position to control the rate of evaporation.…”
Section: Preparation Of Filmsmentioning
confidence: 99%
“…Our results indicate that MTC release from transdermal films followed Higuchi model (r 2 = 0.98-0.99). This observation implies that the drug released from all transdermal films prepared follows matrix diffusion mechanism, in which the rate controlling step is the process of diffusion through matrix polymer base [44][45][46]. The regular release of MTC from all formulations led to prove the homogeneous physical structure of the films.…”
Section: Code Hardness (N) Elasticity (Mj) Cohesiveness Adhesiveness mentioning
confidence: 99%